شذرات من سيرة ذاتية عادية - طبر, بول (Ifpoche, 2022)
When I started writing what later turned into an "autobiography", I was determined to write a mere 'post' from a personal angle on the memory of the outbreak of the civil war in Lebanon on April 13, 1975. Suddenly, I found myself motivated to write more every time I finish writing a new post, and I started to feel that the general question that was guiding my successive writings began to appear in the following form: How did I react to that violent event, and what was its relationship to my family's decision to emigrate to the Australian continent four years before the outbreak of the civil war?Trying to answer this overarching question, I found myself writing successively about my upbringing in Lebanon until the age of 17; about the family I grew up in; the neighborhood and the school I went to; about upper Tripoli, al-Qibba, and downtown Tripoli; about Zgharta-Ehden, the place I originated from. In this context, I started writing about my family migration to Australia, and living, working, and studying in Sydney. And finally, I wrote extensively about my second return to Lebanon around the turn of this century, my working and residing in Beirut, and about leaving work after the uprising of October 17, 2019, and the subsequent general collapse of the country leading to the decision to return permanently to Sydney. During all this, I found myself determined to delve into my personal life and even its intimate often using the socio-anthropological perspective that I had come to possess because of my work in this scientific field. Not only was this usage spontaneous due to my experience in this field, but I also considered using this perspective the biggest challenge I faced during the various stages of writing my autobiography. In other words, how can a graduate and a scholar in sociology and anthropology write his autobiography? I guess, the book in your hands is my answer to this question.